A Case of Tuberculosis of Maxillary Sinus - Ashfak R. Kakeri (Al Ameen Medical College, 2008)
Tuberculosis of the maxillary sinus is rare. Although involvement of long bones and vertebral column is common, its quite uncommon in flat bones. We describe here a case of tuberculosis of the maxillary sinus, and discuss the clinical features and its management.